RHETORIC AND READING COMPREHENSION OR READING SKILLS IN SEARCH OF A CONTENT - Catterson, Jane (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1971)
One of the tasks of what Robinson has called the "inventive methodologist" is the creation of new teaching models. Such models may be drawn from the original research of the methodologist concerned, or they may be formed by drawing together, from various sources, ideas and principles that seem to provide guidelines for new ways of thinking about teaching. The teaching model discussed in the following paper is based, not on the original research of the writer, but on a drawing together of ideas from such psychologists as Bruner, Ausubel and Robinson, such linguists as Pike, and such inventive methodologists as Herber. The resulting amalgam, it is hoped, will provide a frame of reference for some of the skill-building practice being given in the name of teaching reading, and which, it seems, is seldom translated into "real" situations because teachers do not understand well enough the context within which they are teaching.